This isn'´t functioning! Challenging paradigms of functional efficiency in the context of automobile arrangements - Wrbouschek, Markus; Hametner, Katharina (International Review of Theoretical Psychologies, 2026)
Mobility patterns play a crucial role in the context of contemporary eco-crises. Within the context of critical psychologies of the everyday this paper addresses the role that automobile arrangements play in cementing imperial modes of living in the Global north. Departing from conceptual discussions as well as with regard to empirical data from a recent research project, we discuss how appeals to functional efficiency operate in legitimizing the status quo of car-dependent lifestyles. We draw from the work of Gilbert Simondon to develop a conceptual framework that enables re-problematizing self-enclosed patterns of functioning. An understanding of technical objects as relational becoming that require mediation by agents within techno-geographical milieus extending beyond anthropocentric utilities and concerns is developed and exemplified with reference to empirical findings.